Working With Immigrants: A Qualitative Study on the Experiences of Field Workers - Umut Yertum (Sosyal Siyaset Konferansları Dergisi)
This study aims to determine the working conditions, income levels, job security, discrimination, and professional difficulties of social workers who work as field assistants in an international non-governmental organization operating in Turkey. For this purpose, interviews with 15 social workers using semi-structured interview technique were analyzed with the program Maxqda. All experts apart from the project assistants with overtime hours being compensated for as paid leave and work on-call on a 24/7 basis. The social workers, most of whom have undergraduate degrees, have an average of 3.5 years of seniority, and 66% of them earn a monthly income of 16,000 TL or more. Having witnessed death, injury, or rape among the immigrant groups resulted in 40% of the social workers seeking professional support. Lastly, according to the participants, the most important problems encountered in this area are the indefinite work hours due to being on-call and the fixed-term employment contracts due to being project-based.